The Secret world of animals. (Washington, D.C. : National Geographic Society, 1986)
Text and pictures take the reader inside animal homes--used for resting, sheltering from weather, escaping enemies, and raising young.
Includes index.
Bibliography: p. 103.
Keywords: Animals -- Habitations -- Juvenile literature; Animal behavior -- Juvenile literature; Animals -- Habitations